Can a Multistakeholder Prioritization Structure Support Regulatory Decision Making? A Review of Pediatric Oncology Strategy Forums Reflecting on Challenges and Opportunities of this Concept. Issue 3 (8th July 2020) - Karres, Dominik; Lesa, Giovanni; Ligas, Franca; Annunen, Pia; van Dartel, Maaike; Demolis, Pierre; Galluzzo, Sara; Herold, Ralf; van Criekingen, Olga Kholmanskikh; Stoyanova‐Beninska, Violeta; Norga, Koen
Abstract : Timely and successful drug development for rare cancer populations, such as pediatric oncology, requires consolidated efforts in the spirit of shared responsibility. In order to advance tailored development efforts, the concept of multistakeholder Strategy Forum involving industry, academia, patient organizations, and regulators has been developed. In this study, we review the first five pediatric oncology Strategy Forums co‐organized by the European Medicines Agency between 2017 and 2020, reflecting on the outcomes and the evolution of the concept over time and providing an outline of how a "safe space" for multistakeholder engagement facilitated by regulators could be of potential value beyond pediatric oncology drug development.